2011
DOI: 10.1007/s00296-011-2009-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren’s syndrome in Moroccan patients: characteristics, fatigue and quality of life

Abstract: Our aim was to evaluate fatigue and quality of life (QoL) in Moroccan patients with primary Sjögren's syndrome (PSS) and determine their correlates with disease-related parameters. Fifty-seven consecutive patients with PSS according to the American-European Consensus group (AEGG) criteria were included. Demographic, clinical, biological and immunological characteristics for all patients were collected. Xerostomia was demonstrated by histological grading of lower lip glandular biopsy. A Schirmer test was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 37 publications
4
37
1
1
Order By: Relevance
“…In 57 case series of Ibn Yacoub et al. (), it was found that compared to general population, lower performance was found in all SF‐36 scores, including physical problems, role functioning emotional, vitality, and general health scales. In the study of Baturone et al.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In 57 case series of Ibn Yacoub et al. (), it was found that compared to general population, lower performance was found in all SF‐36 scores, including physical problems, role functioning emotional, vitality, and general health scales. In the study of Baturone et al.…”
Section: Discussionmentioning
confidence: 98%
“…In PSS cases without neurological involvement, it was found that there was a significant hypoperfusion at left frontal, left parietal, left temporal, right frontal, and right hippocampal cortex, and also it was shown that there was a strong correlation between the hypoperfusion specified at frontal, parietal, temporal, cingulate, and hippocampal areas, and the dysfunction of the executive functions (Le Guern et al., ). When the brain MRI was normal, it was found that the presence of hypoperfusion in parietal, temporal, and frontal lobes was 56.3% in PSS cases with neuropsychiatric symptoms and findings and 17.6% in PSS cases with no neuropsychiatric symptoms and findings at the brain Tc‐ECD SPECT and this result increased the sensitivity of the brain Tc‐ECD SPECT (Ibn Yacoub et al., ). It was revealed that in PSS cases, there was a correlation between cognitive dysfunction and decreased NAA level and decreased NAA/Cr rate at the subcortical frontal and basal ganglia's white matter and presence of the increased vascular resistance in MCA circulation and this was explained by the subclinical vascular inflammation and endotheliitis in PSS (Morreale et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations